The Impact of Sustainable Certification on Arabica Coffee's Competitiveness and Regional Development in Aceh, Indonesia - ., Fadli; Nasution, Zulkifli; Lubis, Satia Negara; Aritonang, Evawany Yunita (Journal of Ecohumanism, 2024)
This study explores the role of sustainable certification in enhancing the competitiveness and regional development of Arabica coffee in Aceh, Indonesia. By employing Location Quotient (LQ) analysis, the study assesses the coffee sector's economic contribution, while the Policy Analysis Matrix (PAM) evaluates the comparative and competitive advantages of certified Arabica coffee. Data were collected through surveys, interviews, and observations involving 273 respondents from the Central Aceh and Bener Meriah districts, the primary production areas. The findings reveal that these regions possess high LQ values, underscoring the coffee sector's significance. The results indicate that sustainable certification significantly increases farmers' income, with a benefit-cost ratio (R/C ratio) of 3.36 for domestic budgets and 3.46 for social budgets. Additionally, the study finds strong comparative and competitive advantages, with a Domestic Resource Cost Ratio (DRCR) of 0.0089 and a Private Cost Ratio (PCR) of 0.0075. This demonstrates that sustainable certification not only boosts the market position of Aceh's Arabica coffee but also supports broader regional development. The study concludes by recommending continued support for certification initiatives, modern agricultural technology investments, and strategic promotion of Aceh coffee in both domestic and international markets.